AN ANALYZING THE IMPACT PANDEMIC OF COVID-19 TO THE EDUCATION IN INDONESIA: STUDENTS, TEACHERS AND PARENTS - Risca Dwiaryanti; Fadali Rahman (LP2M IAI Al Khairat Pamekasan, 2021)
Pandemic covid-19 has surprised people all over the world. It happen suddenly and give many impacts to all aspects of human’s life including education in Indonesia. Since, the minister of education and culture stated that all he activity of teaching and learning should be done at home by online learning, then it gives some positive and negative impact. The negative impacts are; not all teachers, studemts, or parents have a facility to access internet, nor use IT well, for example theachers who are old or students of pre school still need their parents’ help. Then, not all parent can earn money to buy internet quota. Moreover, the positives impacts are; the students become familiar to use IT and it is safe for them to avoid covid-19 outbreak by studying at home.